Digital game's impacts on students' learning effectiveness of correct medication - Ya-Ming Shiue; Yu-Chiung Hsu (International Journal of Management, Economics and Social Sciences (IJMESS), 2017)
In recent years, considerable concern has arisen over the use of digital games as instructional tools in educational research. However, game-based learning not only enhances students' learning motivation and effectiveness, but also fosters knowledge transfer. Taiwanese people living in rural areas often receive health-related information through television and radio advertisements. However, a lack of correct information leads to incorrect medication usage. Therefore, the purpose of this study is the practical development of a digital game related to correct medication usage. The technology acceptance model was applied to examine the impact of the game-based learning experience. The results showed that the post-test scores for correct medication usage were significantly higher than those obtained in the pre-test and indicated that the digital game could enhance students' learning effectiveness. In addition, perceived ease of use and usefulness had significant impacts on attitude toward the correct medication usage digital game. In conclusion, game-based learning significantly enhanced students' knowledge and abilities related to the correct usage of medication.
Keywords: 330; Game-based learning; correct medication use; health literacy; technology acceptance model